2022
DOI: 10.3389/fnut.2022.1025929
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-linearity in calorie–income relationship in Pakistan

Abstract: This article considers the issue of assessing non-linearity in the relationship between calorie consumption and income using non-parametric and semi-parametric approaches. These methodologies are implemented on the cross-sectional household survey data conducted in Pakistan in 2010–2011. This framework takes account of the heterogeneity among families and potential non-linearity in the relationship. The findings show that the calorie–income elasticity is considerable and statistically significant across estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…These insights can potentially be very useful in the design of a poverty alleviation program [28]. Despite an apparent divergence between calorie-based poverty and income-based poverty trends, income continues to be a powerful determinant of calorie intake [29,30]. Household income plays an important role in moving out from poverty state [26].…”
Section: Urban and Rural Differences (Income Poverty Model)mentioning
confidence: 99%
“…These insights can potentially be very useful in the design of a poverty alleviation program [28]. Despite an apparent divergence between calorie-based poverty and income-based poverty trends, income continues to be a powerful determinant of calorie intake [29,30]. Household income plays an important role in moving out from poverty state [26].…”
Section: Urban and Rural Differences (Income Poverty Model)mentioning
confidence: 99%
“…No study has been found in literature that explains how socioeconomic factors are useful for changes in the consumption of macronutrients between 2 different periods. Some recent studies have also focused on the pattern of food consumption in developing and developed countries [ [21] , [22] , [23] , [24] ]. Mayén et al.…”
Section: Introductionmentioning
confidence: 99%